Kinetic and isotherm evaluation of o-cresol adsorption on activated carbon procured from olive pomace - Choukchou Braham Salima; Taleb Zoubida; Djeziri Soumia; Djellouli Hadja Mebarka (Acta Periodica Technologica, 2023)
This article aims to apply an activated carbon on the adsorption of o-cresol in an aqueous medium. Our work presents a double environmental aspect: On one hand, a valorization of under-natural products, which is the olive pomace and on the other hand, the study of the adsorbent efficiency of the activated carbon resulting from these cores. Activated carbon is prepared with chemical activation of olive pomace using H3PO4. The characterization of this porous material has shown a specific surface area equal to 651 m2/g with the presence of mesopores. Various parameters influencing the adsorption were optimized, mainly the effect of the contact time, initial concentration of o-cresol and pH of the solution were studied. The experimental results show that the sorption equilibrium is reached within 60 min with an adsorption yields of 83.66%. Indeed, the experimental adsorbed quantity of adsorbent is 3.82 mg/g with o-cresol concentration of 50 mg/L, T = 30°C and pH 2.6 for the better adsorption. The adsorption process was also studied by examining Langmuir, Freundlich, Temkin isotherm, and Dubinin-Radushkevich (D-R) isotherm models. The results revealed that the adsorption system followed the pseudo-second order model and the Freundlich model. Several thermodynamic factors, namely, the standard free energy (ΔGads), enthalpy (ΔHads), and entropy (ΔSads) changes, were also calculated. The results demonstrated that the adsorption process is a physical and endothermic. The obtained results are interesting, and applications on other pollutants, in wastewater are in progress.